The Utilization of Architectural Heritage in the Urban Renewal of Benghazi’s Historic City Center (Journal of human and social sciences, 2023)
Preserving a nation’s cultural heritage is an imperative, as it represents a cornerstone of identity and a sense of belonging. Architectural heritage forms a significant part of this legacy, often concentrated in historic city centers characterized by distinct urban identities, such as Benghazi’s historic core. These centers are frequently threatened by modern encroachment, particularly when subjected to neglect or destruction. In Benghazi’s case, its historic center suffered extensive damage during the war (2014–2017), creating an urgent need for urban renewal. This necessity grew even stronger in the years following the war, becoming a pressing demand for local authorities. The study argues that urban renewal in such areas must be grounded in heritage preservation, using architectural heritage as a catalyst for sustainable regeneration. Specifically, the paper focuses on the Italian quarter of Benghazi’s historic center, which features buildings and urban elements of significant architectural, historical, and cultural value. Six focal points were selected for analysis: Souq Al-Hout Square, Salt Square, Silphium Square, Cathedral Square, and Al-Shajara Square. The research provides a historical and urban description of these locations and their associated architectural features. A survey was conducted among Benghazi’s residents to assess their perception of these sites, highlighting whether their importance lies in formal or functional aspects within collective memory. Based on the findings, the study proposes urban renewal strategies rooted in the integration of architectural heritage as a driver for sustainable development. Keywords: Architectural Heritage – Urban Renewal – Sustainability – Benghazi City Center.
Keywords: Urban Identity; Restoration; Sustainable Development; Community Participation; Urban Planning